The effects of soybean variety and inoculants on the physiology of nodulation under field conditions - Rios, Gerson Pereira; Dobereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2014)
In a field experiment conducted at the Uberaba Experiment Station with four soybean varieties and five inoculants, nodule numbers, their total weight and mean weight were determined at different stages of plant development. There were significant differences between inoculants on nodule number and significant variety effects on total and mean nodule weight. The varieties which produced higher nodule numbers also possessed smaller sized nodules. Maximal nodule numbers were reached between 49 and 64 days after planting depending on the vegetative cycle of the variety, and on the inoculant. The best inoculants continued to form nodules until 64 days after planting. Mean nodule size varied little with the inoculant but one early variety produced significantly larger nodules than the others. Total nodule weight increased until 64 days after planting and there were significant differences between inoculants and varieties.